Tinjauan Hukum Mengenai Daluwarsa Gugatan Pemutusan Hubungan Kerja oleh Pemberi Kerja dan Implikasinya terhadap Kepastian Hukum dan Perlindungan terhadap Pekerja. (Studi Kasus Putusan Nomor 637K/Pdt.sus-PHI/2025 Jo. 139/Pdt.sus-PHI/2024/PN Bdg) - Kartika Sandra Kirani Anggara; Robby Tejamukti (LPPM Iblam School of Law, 2026)
Termination of Employment (TOE) constitutes a complex form of industrial relations dispute, as it involves the interests of both workers and employers who are equally protected by law. To ensure legal certainty and prevent prolonged disputes, Law Number 2 of 2004 on the Settlement of Industrial Relations Disputes regulates the statute of limitations for filing termination of employment claims. However, this provision only limits the right of workers to file a claim within one year from the receipt of the termination decision, without imposing a similar time limit on employers. This condition potentially creates an imbalance in legal protection and contradicts the principle of equality before the law.This research aims to analyze the regulation of the statute of limitations for termination of employment claims and its application in Supreme Court Decision Number 637 K/Pdt.Sus-PHI/2025 in conjunction with Decision Number 139/Pdt.Sus- PHI/2024/PN Bdg.